DISTRIBUSI PUPUK BERSUBSIDI DI KABUPATEN BANTUL PROVINSI DAERAH ISTIMEWA YOGYARTA - Agus Dwi Nugroho; Abi Pratiwa Siregar; Erlinda Andannari; Yahya Shafiyudin; Julia Inka Christie (Faculty of Animal and Agricultural Science, Diponegoro University, 2018)
The purpose of this study was to know the availability and needs, to evaluate and to formulate the suggestion for fertilizer distribution in Bantul Regency Daerah Istimewa Yogyakarta Province. The study was conducted in May and June 2017. Research respondents are distributors, retailers, farmer groups, and farmers. Trend analysis is used to determine the availability and demand of fertilizer. The effectiveness of fertilizer distribution was determined by the six precise of the distribution of fertilizer while efficiency was measured by using marketing margin. The results showed that the availability and the need of fertilizer is fluctuating with the tendency is scarcity in few months. As a whole, the distribution of fertilizer has been quite effective and efficient but sometimes the amount and the price of fertilizer for farmers was not correct and the distribution was not accordance with the regulation. The problems in the distribution of fertilizer are the incomplete database of the availability and the need of fertilizer, the retailers were not selling the fertilizer to the farmer group while the farmers were not buying through from the farmer groups, the location of the retailer is too far from the farmer and the price of fertilizer in over of highest price recommended by the government.Kata kunci : Kabupaten Bantul; efektif; efisien; pupuk bersubsidi